Internal control and SMEs' sustainable growth: The moderating role of multiple large shareholders - Liangcheng Wang; Yining Dai; Yuye Ding (Journal of Risk and Financial Management, 2019)
Small and medium enterprises (SMEs) face more risks for sustainable growth due to a lack of resources than large firms in emerging economies. Hence, it is more likely for SMEs to look to risk management for survival in turbulent markets. As a tool of risk management, whether internal control indeed has contributions to the sustainable growth of SMEs, particularly conditional on multiple large shareholders, is empirically unexplored. Using a sample of SMEs listed in China, this study examines the relationship between internal control and sustainable growth, and assesses a moderating role of multiple large shareholders. The results show that effective internal control significantly promotes SMEs to achieve sustainable growth, and the effect is moderated by multiple large shareholders, suggesting that the role of internal control is more prominent in SMEs with multiple large shareholders. These results are robust to a battery of sensitivity tests. This study extends the literature by providing empirical evidence on the role of internal control in SMEs' sustainable growth.
Keywords: 330; internal control; multiple large shareholders; SMEs; sustainable growth